Effects of ubiquinol with fluid resuscitation following haemorrhagic shock on rat lungs, diaphragm, heart and kidneys. Issue 7 (11th June 2014) - Bennetts, Paul; Shen, Qiuhua; Thimmesch, Amanda R.; Diaz, Francisco J.; Clancy, Richard L.; Pierce, Janet D.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? What are the effects of administering ubiquinol (reduced form of co‐enzyme Q10) following haemorrhagic shock on leucocyte mitochondrial superoxide, diaphragmatic hydrogen peroxide concentration and apoptosis in the lungs, diaphragm, heart and kidneys? What is the main finding and its importance? The administration of ubiquinol attenuated damage to the lungs, diaphragm, heart and kidneys following haemorrhagic shock and fluid resuscitation. Leucocyte mitochondrial superoxide was reduced, while hydrogen peroxide and apoptosis in the diaphragm decreased, as did apoptosis in the lungs, heart and kidneys. These findings suggest that ubiquinol could be a potential antioxidant used to reduce the reperfusion injury following haemorrhagic shock. Haemorrhagic shock (HS) and fluid resuscitation can lead to increased reactive oxygen species (ROS), contributing to ischaemia–reperfusion injury and organ damage. Ubiquinol is a potent antioxidant that decreases ROS. This study examined the effects of ubiquinol administered with fluid resuscitation following controlled HS. Adult male Sprague–Dawley rats were randomly assigned to treatment [ubiquinol, 1 mg (100 g body weight)−1] or control groups. Rats were subjected to 60 min of HS by removing 40% of the total blood volume to a mean arterial pressure ∼45–55 mmHg. The animals were resuscitated with blood and lactated Ringer solution, with or without ubiquinol, and monitored for 120 min. At the end of the experiments, the rats were killed and the lungs, diaphragm, heart and kidneys harvested. Leucocytes were analysed for mitochondrial superoxide at baseline, end of shock and 120 min following fluid resuscitation using MitoSOX Red. Diaphragms were examined for hydrogen peroxide using dihydrofluorescein diacetate and confocal microscopy. The apoptosis in lungs, diaphragm, heart and kidneys was measured using fluorescence microscopy with acridine orange and ethidium bromide. Leucocyte mitochondrial superoxide levels were significantly lower in rats that received ubiquinol than in the control animals. Production of hydrogen peroxide and apoptosis were significantly reduced in the organs of rats treated with ubiquinol. These findings suggest that ubiquinol, administered with fluid resuscitation after HS, attenuates ROS production and apoptosis. Thus, ubiquinol is a potent antioxidant that may be used as a potential treatment to reduce organ injury following haemorrhagic events.